The Legal Status of Surrogacy Agreement According to Contract Law in Indonesia - Rahayu Gorda, A.A.A.Ngr.Sri; Sutrisni, Ni Ketut Elly; Mas Triwulandari, I Gusti Agung Ayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 4 (2019)DO - 10.24843/JMHU.2019.v08.i04.p03, 2019)
Indonesia does not yet have specific rules regarding surrogate mother or surrogacy agreement. The purpose of this paper is to analyze the position of surrogacy agreement according to contract law in Indonesia. It is a normative legal research that raising legal issues regarding the position of surrogacy agreement according to contract law in Indonesia. The results of the study showed that according to the elements of the legality of the agreement as stipulated in Article 1320 of the Indonesian Criminal Code, the surrogacy agreement did not fulfill the objective conditions of the agreement that entails a null and void. Besides, the surrogacy agreement did not fulfill the elements of propriety and custom and was prohibited by the Law